Environmental suitability of agricultural lands and water harvesting in the Balkian Valley basin - Salman, Neeran Mahmoud; Abbas, Ahmed Kazem (Al-Adab Journal, 2022)
The Balkyan Valley Basin is located in northern Iraq at the Erbil Governorate, between latitude (36 ° 39'59.0 ") and (36 ° 56'42.0") north, and longitude (44 ° 17'17.0 ") and (44 ° 54'25.0") To the east, with an area of ​​(1052.14 km2), the researchers studied the natural situation of the basin to create a database for it that is used to map the environmental suitability of agricultural lands within the boundaries of the research area, followed by the study of the surface runoff of the basin and estimation of its quantity in the area and then urges the possibility of constructing a dam for the purpose of water harvesting. The research aims to study the facilities provided by the natural environment for the agricultural aspect, as well as the elements it provides for water harvesting for the purpose of providing the necessary amount of water. The annual water flow is estimated at about (691) million cubic meters as an average for the years (2000 - 2020), with the possibility of constructing a dam with a storage volume of (548 m3) with a basin area (776 km2) and an annual flow volume of (514 m3).